# algebra

posted by ASHLY

multiply: (w+p)(w^2-wp+p^2)

1. Bosnian

(w+p)(w^2-wp+p^2)
=w^3-w^2*p+w*p^2+p*w^2-w*p^2+p^3
=w^3+p^3

## Similar Questions

1. ### Pre-Algebra

inequality 0.75x>3 Multiply both sides of the inequality by 4/3 if you want to know what x is. from where did you get 4/3 to multiply to find x. How do you know that?
2. ### someone help

my post is still on this page as algebra, could someone elaborate on what bobpursley tried to help me with. See your original post. I am guessing you are referring to your question 5)Simplify:(5x-4)^2 and your answer= 25x^2 - 16 (5x-4)^2 …
3. ### need guidance on an algebra problem

20 x+3(y-1)=11 2(x-y)+8y = 28 multiply out 20 x+3y-3=11 - Is this correct?
4. ### Algebra Sq Rt

to multiply the sq rt of 3 cubed by the sq rt of 9 cubed I first need to factor them?
5. ### Algebra

16. I am supposed to multiply the matrices B and C by each other B is: 7 6 2 -3 -1 8 9 5 and C: 0 8 -2 1 Would someone mind showing me how to multiply CB?
6. ### Algebra

89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, and this is the reply I got from someone: multiply both sides by 7 6x-42=-14 add 42 to each side 6x=28 x=14/3 But I don't get how this is done because to eliminate …
7. ### Math

The problem to solve is: (x+20)(x-12)(x+4)>0 but I can't figure out how to do this right so I left off the >0 and tried to solve the equation. x+20 evaluates to x+20 x-12 evaluates to x-12 Multiplying x+20 by x-12 is a classic …
8. ### algebra II

Select the best possible first step to solving the system by first eliminating the y variable. x + 8y = –4 2x – 4y = –13 Multiply the first equation by 2. Multiply the second equation by 2. Multiply the first equation by –2. …
9. ### algebra

Solve. x/9-1/7=26/63 STEP 1: The LCM is _________ To clear denominators, multiply each side of the equation by the LCM. _______/1 (x/9-1/7)=__________/1 multiply 26/63. STEP 2: Use the Distributive Property. _____/1 multiply x/9 - …
10. ### Algebra 1

I pretty much know this problem 4y+2x=18 3x+6y=26 multiply -3= -6x+-12y= -54 multiply 2 = 6x+-12= 52 The answer is -2 but I am not sure what to do next since both x and y were canceled out.

More Similar Questions